Simulasi Numerik Kelajuan dan Periode Orbit Satelit Mengelilingi Bumi - Iman Noor; Andry Fitrian; Ahmad Jahrudin (UNIVERSITAS INDRAPRASTA PGRI, 2021)
Numerical simulation of the satellites’s orbital velocity and orbital period on the earth has been performed. This research aimed to study satellites’s orbital velocity and orbital period on the earthbased on position function. Velocity equation has been gotten from modification equation of centripetal force and equation of earth’s gravitational force. Through numerical calculation of orbital velocityand orbital period equation by function discretization, we got that the velocity and period of satellite at height of 30000 km above the earth’s surface are 3.31 km/s and 19.18 hours, respectively.